2020: heritage, the pandemic and the journal - Ferreira, Tiago Miguel; Sequeira, Sílvia O.; Claro, Ana; Miller, Ana Zélia; Figueiredo, Elin (Conservar Património, 2021)
2020 was an untypically difficult year. The global COVID-19 pandemic has forced the closure of various sectors of activity, including universities, laboratories and businesses, impelling researchers and technicians to temporarily halt their research or, at their best, to develop it in a limited way. Less recognised but equally significant was the direct impact of COVID-19 on the preservation and protection of cultural heritage. Online: 2021-2-10 Publication: 2021-2-10